Gametocyte clearance dynamics following oral artesunate treatment of uncomplicated falciparum malaria in Malian children - Djimde Abdoulaye A.; Maiga Amelia W.; Ouologuem Dinkorma; Fofana Bakary; Sagara Issaka; Dembele Demba; Toure Sekou; Sanogo Kassim; Dama Souleymane; Sidibe Bakary; Doumbo Ogobara K. (Parasite, 2016)
Artemisinin-based combination therapies decrease Plasmodium gametocyte carriage. However, the role of artesunate in monotherapy in vivo, the mechanisms involved, and the utility of gametocyte carriage as a potential tool for the surveillance of antimalarial resistance are poorly understood. In 2010–2011, we conducted an open-label, prospective efficacy study of artesunate as monotherapy in children 1–10 years of age with uncomplicated falciparum malaria in Bougoula-Hameau, Mali. Standard oral doses of artesunate were administered for 7 days and patients were followed up for 28 days. The data were compared to a similar study conducted in 2002–2004. Of 100 children enrolled in the 2010–2011 study, 92 were analyzed and compared to 217 children enrolled in the 2002–2004 study. The proportion of gametocyte carriers was unchanged at the end of treatment (23% at baseline vs. 24% on day 7, p = 1.0) and did not significantly decline until day 21 of follow-up (23% vs. 6%, p = 0.003). The mean gametocyte density at inclusion remained unchanged at the end of treatment (12 gametocytes/μL vs. 16 gametocytes/μL, p = 0.6). Overall, 46% of the 71 initial non-carriers had gametocytes detected by day 7. Similar results were found in the 2002–2004 study. In both studies, although gametocyte carriage significantly decreased by the end of the 28-day follow-up, artesunate did not clear mature gametocytes during treatment and did not prevent the appearance of new stage V gametocytes as assessed by light microscopy. Baseline gametocyte carriage was significantly higher 6 years after the deployment of artemisinin-based combination therapies in this setting.